Os saberes e fazeres dos coordenadores pedagógicos: a sua importância na Formação continuada dos educadores da Educação Infantil - FRANCO, Rita Maria Sousa (2021)
The pedagogical coordinators knowledge and doings and your importance in the continued formation of the Child Education Educators, research developed in the professional master’s degree. The investigation leaved of some central questions: What the understanding of the Municipal Secretary of Education (SEMED’s) continued formation for the pedagogical coordinators formation? What the conceptions theoretical-methodological of continued formation are present in the formations at work of the Child Education coordinators pedagogical? Which way is developed by pedagogical coordinators the continued formation of coordinators to act in the continued formation of coordinators in the formation whit the Child Education Educators? How to prepare a notebook of pedagogical guidance of continued formation so that can contribute whit the Child Education pedagogical coordinators work? From these inquiries, was thought the general objective which consists: analyze how the Child Education pedagogical coordinators experience in the continued formation of educators, starting from formative spaces promoved by SEMED, whit a view the construction on one notebook of pedagogical guidance of continued formation. As ramifications were added the specific objectives: identify the conceptions theoretical-methodological of formation of the Child Education pedagogical coordinators; check how is developed the continued formation of Child Education coordinators and educators; build with the coordinators who minister the formations a pedagogical continued formation notebook in order to contribute with the Child Education coordinators work. For the reach than propose, spear hand of methodological research. The Your research subjects were the Child Education pedagogical coordinators, that offer and are responsible by continued formation of those teachers that act at Child Education. The research was based in the next theoreticals: Alarcão (2005), Ariès (2011), Kramer et al. (2019), Kuhlmann Júnior (2011), Launde (2013), Nóvoa (2000, 2001), Oliveira (2005), Pimenta (1996, 1999), Pimenta e Anastasiou (2002), Schön (2000) and Tardif (2012, 2014).Already like methodology was used the literature revision researches, of the type art´s state and documentary. From the viewpoint of your objectives, the present research had exploratory and descriptive character, were used data production and generation instruments: semi-structured interviews, Google Forms formulary and Google Meetu. The results founded at research show us the continued formation importance for a construction of a good practice, we highlighted the knowledge and doings building at continued formation of the Child Education coordinators. We expect that the research be likely to serve like base for other investigations, about the studied thematic.